2016
DOI: 10.1021/acsami.5b11091
|View full text |Cite
|
Sign up to set email alerts
|

AIE-Active Tetraphenylethylene Cross-Linked N-Isopropylacrylamide Polymer: A Long-Term Fluorescent Cellular Tracker

Abstract: There is a great demand to understand cell transplantation, migration, division, fusion, and lysis. Correspondingly, illuminant object-labeled bioprobes have been employed as long-term cellular tracers, which could provide valuable insights into detecting these biological processes. In this work, we designed and synthesized a fluorescent polymer, which was comprised of hydrophilic N-isopropylacrylamide polymers as matrix and a hydrophobic tetraphenylethene (TPE) unit as AIE-active cross-linkers (DDBV). It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 43 publications
0
58
1
Order By: Relevance
“…This suggests that TPE‐CS is an excellent candidate for long‐term cell tracing. In addition, based on the temperature‐sensitive characteristics of polymers, two kinds of temperature‐sensitive AIE‐based fluorescent probes, TPE‐PNIPAM and TPE‐PNIPAm, have been developed and applied for long‐term cell tracing. For example, Zhang et al have reported temperature‐sensitive NPs made from self‐assembly of TPE‐PNIPAM in water (Figure d) .…”
Section: Lighting Up Cellular Processesmentioning
confidence: 99%
“…This suggests that TPE‐CS is an excellent candidate for long‐term cell tracing. In addition, based on the temperature‐sensitive characteristics of polymers, two kinds of temperature‐sensitive AIE‐based fluorescent probes, TPE‐PNIPAM and TPE‐PNIPAm, have been developed and applied for long‐term cell tracing. For example, Zhang et al have reported temperature‐sensitive NPs made from self‐assembly of TPE‐PNIPAM in water (Figure d) .…”
Section: Lighting Up Cellular Processesmentioning
confidence: 99%
“…In 2016, Ishiwari et al introduced TPE molecules into polyacrylic acid hydrogels, showing enhanced fluorescence emission after adding Ca 2+ due to significant chain folding thereof [22]. Later, in the same Polymers 2020, 12, 551 2 of 12 year, Lei et al designed temperature-responsive polymer gels, whose fluorescence switch was driven by a combination of poly(N-isopropylacrylamide) (PNIPAm) and the AIE effect [23].…”
Section: Introductionmentioning
confidence: 99%
“…18,19 As a result, molecular rotations can be restrained to some extent; this leads to more emissive polymers not only in the powder but also in the solution state. 20,21 Therefore, polymerization-promoted AIE systems have been designed and developed in recent years. [22][23][24][25] By integrating the desirable AIE feature with conjugated polymer characteristics, attractive materials could be generated.…”
Section: Introductionmentioning
confidence: 99%